Pustaka in a box: bridging the digital gap - Japri Bujang, Masli; Johari, Abdullah; Musa Ayub, Abd Rahman (2017)
At about 124,450 km 2, Sarawak is the largest state in the Federation of Malaysia. The total population of Sarawak is about 2.6 million and that gives a population density of about 21 per km 2. This is a real challenge in providing library services even online as the digital gap exist not just because of geography but also due to economic reasons.